Disinfection methods for preventing COVID-19 infections in healthcare settings: A rapid review - Joseph Okebe; Atana Ewa; Ememobong Aquaisua; Obasesam A. Ikpi; Ella Olughu; Ebere C. Chukwuemelie; Chukwudi Oringanje; Tochi Okwor; Martin Meremikwu (Journal of Public Health in Africa)
Background: Disinfectant sprays and wipes reduce the risk of infection from contaminated surfaces and materials in healthcare facilities. To support guideline updates, evidence on surface disinfection against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are needed.